2021
DOI: 10.1111/1440-1681.13490
|View full text |Cite
|
Sign up to set email alerts
|

Low field magnetic stimulation promotes myelin repair and cognitive recovery in chronic cuprizone mouse model

Abstract: Background Multiple sclerosis (MS) is an inflammatory demyelinating disease featured with neuroinflammation, demyelination, and the loss of oligodendrocytes. Cognitive impairment and depression are common neuropsychiatric symptoms in MS that are poorly managed with the present interventions. Objective This study aimed to investigate the effects of low field magnetic stimulation (LFMS), a novel non‐invasive neuromodulation technology, on cognitive impairment and depressive symptoms associated with MS using a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…Both MS and major depressive disorder share the common pathophysiology of demyelination of CNS regions and are associated with neuro-inflammation processes (55,56). Indeed, previous CPZ mouse models have reported depression-like symptoms and myelin deficiency (19,30) demonstrating a possible correlation between depression and demyelination of the CNS. In the present study, it was demonstrated that mice fed with CPZ exhibited markedly reduced MBP staining density within the PFC and HPC after only 3 weeks, which suggested that there was a possible link between early depression and myelin damage in this demyelinating disease model.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Both MS and major depressive disorder share the common pathophysiology of demyelination of CNS regions and are associated with neuro-inflammation processes (55,56). Indeed, previous CPZ mouse models have reported depression-like symptoms and myelin deficiency (19,30) demonstrating a possible correlation between depression and demyelination of the CNS. In the present study, it was demonstrated that mice fed with CPZ exhibited markedly reduced MBP staining density within the PFC and HPC after only 3 weeks, which suggested that there was a possible link between early depression and myelin damage in this demyelinating disease model.…”
Section: Discussionmentioning
confidence: 99%
“…The LFMS device is composed of two 360 mm-diameter coils and a control center that generates intermittent gamma stimulation waves (Beijing Antis Biotech Co., Ltd.). The LFMS parameter settings were based on our previous in vivo and in vitro studies (28)(29)(30)37). Briefly, the magnetic field alternated every 2 min between approximate and linear gradients.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations